2008
DOI: 10.1007/s00251-007-0262-2
|View full text |Cite
|
Sign up to set email alerts
|

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project

Abstract: The human major histocompatibility complex (MHC) is contained within about 4 Mb on the short arm of chromosome 6 and is recognised as the most variable region in the human genome. The primary aim of the MHC Haplotype Project was to provide a comprehensively annotated reference sequence of a single, human leukocyte antigen-homozygous MHC haplotype and to use it as a basis against which variations could be assessed from seven other similarly homozygous cell lines, representative of the most common MHC haplotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
258
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(272 citation statements)
references
References 50 publications
10
258
0
4
Order By: Relevance
“…Otherwise, we have found that telomeric C4 genes of multimodular structures usually code for a C4A isotype protein, which is in agreement with previous assumptions deducted from sparse sequencing data 2 and results of the MHC Haplotype Project. 20 Here we also give evidence of the assumption that C4A genes are almost always long and that there is an approximately equal chance that a C4B gene belongs to the short or the long variant. 21 Former RCCX-related studies sometimes also detected dosage ratios of TNX and CYP21 active genes and pseudogenes.…”
Section: (L)-b(s)-b(s) and B(l)-a(s)-b(s)mentioning
confidence: 54%
“…Otherwise, we have found that telomeric C4 genes of multimodular structures usually code for a C4A isotype protein, which is in agreement with previous assumptions deducted from sparse sequencing data 2 and results of the MHC Haplotype Project. 20 Here we also give evidence of the assumption that C4A genes are almost always long and that there is an approximately equal chance that a C4B gene belongs to the short or the long variant. 21 Former RCCX-related studies sometimes also detected dosage ratios of TNX and CYP21 active genes and pseudogenes.…”
Section: (L)-b(s)-b(s) and B(l)-a(s)-b(s)mentioning
confidence: 54%
“…Many of the HLA alleles were first identified serologically and gave rise to a complex and often inconsistent nomenclature. Recent extensive efforts were made at mapping the serologic types to DNA sequences and the genetic architecture of the MHC is now much better understood (Allcock et al, 2002;Stewart et al, 2004;Miretti et al, 2005;de Bakker et al, 2006;Horton et al, 2008). As a consequence, the genetic basis of the serotypes has been defined and a consistent nomenclature has finally come into focus that will help advance further study of the MHC (http:/ /hla.alleles.org/).…”
Section: The Mhc and Ms Susceptibilitymentioning
confidence: 99%
“…155 Similarly, several other class II loci including HLA-DRB1 and HLA-DQA1 are known to show haplotypic variation at splice sites, which may affect expression at a post-transcriptional level. 156 A growing number of reports highlight the role of DNA sequence variation in modulating alternative splicing, which can contribute to disease susceptibility. 157 The MHC class II region has already provided one of the clearest examples of a SNP modulating alternative splicing resulting in common disease through the work of Valentonyte et al (2005) 158 on genetic determinants of sarcoidosis, a chronic granulomatous condition.…”
Section: Mhc Class II Expression Polymorphism and Disease L Handunnementioning
confidence: 99%